2018
DOI: 10.3389/fmicb.2018.01462
|View full text |Cite
|
Sign up to set email alerts
|

Sewage Sludge Microbial Structures and Relations to Their Sources, Treatments, and Chemical Attributes

Abstract: Sewage sludges generation and their disposal have become one of the greatest challenges of the 21st century. They have great microbial diversity that may impact wastewater treatment plant (WWTP) efficiency and soil quality whether used as fertilizers. Therefore, this research aimed to characterize microbial community diversity and structure of 19 sewage sludges from São Paulo, Brazil, as well as to draw their relations to sludge sources [domestic and mixed (domestic+industrial)], biological treatments (redox c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
61
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(75 citation statements)
references
References 81 publications
11
61
2
1
Order By: Relevance
“…As it was previously stated by Cydzik-Kwiatkowska and Zielińska ( 2016 ) and Nascimento et al ( 2018 ) also in the case of this research, the change of feeding wastewater can be the reason of the class proportion shift. It could be caused by the concentration changes in organic matter or recalcitrant substances.…”
Section: Resultssupporting
confidence: 77%
“…As it was previously stated by Cydzik-Kwiatkowska and Zielińska ( 2016 ) and Nascimento et al ( 2018 ) also in the case of this research, the change of feeding wastewater can be the reason of the class proportion shift. It could be caused by the concentration changes in organic matter or recalcitrant substances.…”
Section: Resultssupporting
confidence: 77%
“…It has also been reported that recalcitrant and toxic pollutants, such as heavy metals and antimicrobial agents, in biological treatment plants limited the microbial diversity (Balcom et al, 2016). Other factors considered detrimental are, influent characteristic, pH and dissolved oxygen (Nascimento et al, 2018;Zou et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In TP02 the relative high abundance of Firmicutes was observed, which is versatile in degrading a vast array of environmental substrate [17]. They are involved in metabolic pathways responsible for producing volatile fatty acids, which can be utilized by other group of microbes [18]. Compared to previous reports the Proteobacteria was detected as the most dominant phylum in various wastewater treatment plants [19].…”
Section: Discussionmentioning
confidence: 87%